Sobre a influência de fosfinas e do ligante isocianida de p-Toluenosulfonilmetila na citotoxicidade de compostos de Ru(II) - Silveira, Rafael Gomes da (2018)
The main objective of the present work was to obtain new Ru(II) complexes with lingans diimino, phosphinic and isocyanide p-toluenesulfonylmethyl, to characterize them by diverse physical and spectroscopic techniques, to study the interaction with biomolecules DNA and human serum albumin (HSA), besides to evaluated their cytotoxic properties. In this way, we reported the synthesis of fourteen new complexes and the characterization by elemental analysis, cyclic voltammetry, molar conductance, ultraviolet (UV-vis) spectroscopy, infrared spectroscopy (FT-IR), nuclear magnetic resonance (31P{1H}, 1H, 13C {1H}, DEPT-135, COSY, HMBC and HSQC) and Single crystal X-ray diffraction, when possible to obtain single crystal. For the complexes containing only diimine and phosphinic ligands, there were important electronic and steric effects caused by -stacking interactions. Such effect lead to a differentiated behavior in the hydrogens of the phosphinic phenyl groups in the NMR experiments, it was also possible to observe the same effect by crystallography of X-rays and by DFT calculations. Studies of interaction of complexes with DNA by viscosity measurements indicate that the compounds interact poorly with this biomolecule. Two compounds with diiminic phosphinic linker and the p-toluenesulfonylmethyl isocyanate ligand were selected for interaction studies with gel electrophoresis DNA and competitive assay with Hoescht 33258, where the results indicates that compounds interacting electrostatically and/or by the minor groove of the DNA. The HSA interaction studies, carried out by fluorimetric titrations, show that both compounds present interaction constants (Kb) on the order of 104-106, indicating moderate to strong interaction with this protein. For all cases, the interaction mechanism is static. Cytotoxicity data in human tumor cell lines A549 (lung) and DU-157 (prostate) and non-tumor MCR-5 (lung), show that the compounds bearing the p-toluenesulfonylmethyl isocyanide ligand are the most promising, showing up to 140 times more active than the reference drug and up to 3 times more selective.